3-D sloshing of liquid filled laminated composite cylindrical tank under external excitation. (1st November 2021) - Tiwari, Pratik; Maiti, Dipak Kumar; Maity, Damodar
Abstract: A new three dimensional finite element formulation is developed for the analysis of sloshing of liquid inside a partially filled laminated composite cylindrical tank under external excitations. Direct coupling method is adopted for efficient fluid–structure interaction between tank and liquid. The tank structure is modelled using 8 noded 3-D degenerated shell elements and the liquid inside tank is modelled using 20 noded brick elements. Experiments were conducted to validate the developed formulation. The results generated from developed formulation are in close agreement with the results available in open literature and the results obtained from experiment. Parametric studies are conducted by varying the tank thickness, ply orientation, and water level inside the tank to understand their effect on slosh height. Composite tanks are subjected to harmonic and seismic (Koyna earthquake 1967) loading for the parametric study. Highlights: A new 8-noded degenerated shell element is developed for cylindrical composite tank and is used in the fluid–structure interaction formulation. Fluid formulation under dynamic excitation is validated with experiments. Direct coupling method is employed to accurately analyse the fluid–structure interaction effect. Sloshing of liquid filled composite tank is studied under both harmonic and seismic excitations which may be of interest to other researchers. A parametric study is conducted for various ply orientations, tank thicknesses, tank height, tank radius, and height of water inside tank.